Two New Quadrilateral Elements Based on Strain States - Mohammad Rezaiee-Pajand; Majid Yaghoobi (Civil Engineering Infrastructures Journal, 2015)
In this paper, two new quadrilateral elements are formulated to solve plane problems. Low sensitivity to geometric distortion, no parasitic shear error, rotational invariance, and satisfying the Felippa pure bending test are characteristics of these suggested elements. One proposed element is formulated by establishing equilibrium equations for the second-order strain field. The other suggested element is obtained by establishing equilibrium equations only for the linear part of the strain field. The number of the strain states decreases when the conditions among strain states are satisfied. Several numerical tests are used to demonstrate the performance of the proposed elements. Famous elements, which were suggested by other researchers, are used as a means of comparison. It is shown that these novel elements pass the strong patch tests, even for extremely poor meshes, and one of them has an excellent accuracy and fast convergence in other complicated problems.